2016
DOI: 10.1071/an14111
|View full text |Cite
|
Sign up to set email alerts
|

Egg quality and production performance of laying hens injected with growth hormone and testosterone in the late phase of production

Abstract: In this study, 160 73-week-old laying hens (HyLine W-36) were used to investigate the changes in production performance and egg quality parameters of aged laying hens after injection of different doses of growth hormone (GH) and a fixed dose of testosterone (Ts). The hens were weighed individually, placed in laying cages and then randomly assigned to four treatments with four replicates of 10 birds each, in a completely randomised design. The experiment was started at the 75th week and lasted until the 82nd we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
4
6
1
Order By: Relevance
“…The average CVs observed for shell weight and shell thickness suggest uniformity in shell quality across the experimental period. These were similar to those observed in the control group of the study by Mohammadi et al [ 26 ], as well as in the study of early-laying hens reported by Roberts et al [ 18 ]. There was, however, a 15% CV for shell breaking strength.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The average CVs observed for shell weight and shell thickness suggest uniformity in shell quality across the experimental period. These were similar to those observed in the control group of the study by Mohammadi et al [ 26 ], as well as in the study of early-laying hens reported by Roberts et al [ 18 ]. There was, however, a 15% CV for shell breaking strength.…”
Section: Discussionsupporting
confidence: 91%
“…The CV of 3% for yolk index from this study suggests uniformity in yolk quality in early-laying hens between 25 and 30 weeks of age. The average yolk index in the current study was higher than that recorded by Mohammadi et al [ 26 ]. Yolk color is an important visual measure of egg quality which is linked to consumer preference [ 27 ].…”
Section: Discussioncontrasting
confidence: 90%
“…Immediately after slaughtering, whole ovary with follicular hierarchy and oviduct were removed in different stage of egg fromation (Table 1). Ovary weight, the weight of the first, second, third, fourth and fifth largest follicles were measured by Mohammadi and Ansari-Pirsaraei (2016). The oviduct weight, total length of oviduct, length of individual parts of oviduct were considered by modified method of Halaj (1983).…”
Section: Methodsmentioning
confidence: 99%
“…While the highest values of the LBW and BWG were recorded in the groups injected with 200 μg Ts, or GA 3 , / Kg BW followed by the same level of RJ (20-48 Wks of age) when compared to the control group (Table 3). The increase in weight due to RJ, GA3 and Ts has effects similar to that of estrogen on hen body weight (Hiba, 2010;Elkomy et al, 2007 andMohammadi, 2015). From the oldest to the most recent they were showing that the LBW and BWG of the female chicks injected with 200 μg RJ, GA 3 and Ts increased compared to the control group.…”
Section: Productive Performancementioning
confidence: 97%